E-Beacon Card Training Based Application Internet Of Things (IOT) in The School Environment - Imelda Uli Vistalina Simanjuntak; Yosy Rahmawati; Ketty Siti Salamah; Akhmad Wahyu Dani; Yuliza Yuliza (LPPM Universitas Muhammadiyah Tasikmalaya, 2023)
At that time, SMK Yadika 11 Jatirangga Bekasi still needed help communicating announcements within the school. In addition to being expensive, buying an intercom is also less effective during the teaching and learning process due to noise pollution. Therefore the PPM Team at Mercu Buana University wanted to provide a solution by introducing Internet of Things (IoT) technology on one of the Bluetooth ebacon devices. eBeacon Card is a Bluetooth Low Energy transmitter connected to various electronic devices. This device will be connected via a short message to each person's cell phone, such as an SMS notification. In this training, two eBeacon Cards uses, which should be applicable in two rooms with a radius of 20 m. However, due to space limitations, both are installed in one room. So that the target information announcement target can receive data from both eBeacon cards with the same announcement display twice. Some of the outputs used in evaluating this training were that they understood the IoT process, how to install and create eBeacon, and could use it for other needs such as announcements, advertisements, etc.